2019
DOI: 10.1111/trf.15463
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell alloimmunization is associated with lower expression of FcγR1 on monocyte subsets in patients with sickle cell disease

Abstract: BACKGROUND: Despite the clinical significance of red blood cell (RBC) alloantibodies, there are currently no laboratory tests available to predict which patients may be at risk of antibody formation after transfusion exposure. Given their phagocytic and inflammatory functions, we hypothesized that differences in circulating monocytes may play a role in alloimmunization. STUDY DESIGN AND METHODS: Forty-two adultswith sickle cell disease (SCD) were recruited, with data extracted from the electronic medical recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
4
1
Order By: Relevance
“…Given the role that monocytes play in immune responses, a recent study hypothesized that FcγR1 (CD64) expression on monocytes may be associated with RBC alloimmunization status in people with SCD. Contrary to the hypothesis, lower CD64 expression was observed on classical (CD64+CD14 high CD16 low ) and intermediate circulating monocytes (CD64+CD14 high CD16 high ) in alloimmunized people with SCD compared to non-alloimmunized people ( 80 ).…”
Section: Characteristic Of Cell Subsets As Related To Alloimmunizatiocontrasting
confidence: 76%
See 1 more Smart Citation
“…Given the role that monocytes play in immune responses, a recent study hypothesized that FcγR1 (CD64) expression on monocytes may be associated with RBC alloimmunization status in people with SCD. Contrary to the hypothesis, lower CD64 expression was observed on classical (CD64+CD14 high CD16 low ) and intermediate circulating monocytes (CD64+CD14 high CD16 high ) in alloimmunized people with SCD compared to non-alloimmunized people ( 80 ).…”
Section: Characteristic Of Cell Subsets As Related To Alloimmunizatiocontrasting
confidence: 76%
“…In addition, interleukin-6 receptor signaling has been shown to impact RBC alloimmunization in a murine model ( 103 ). Overall serum levels of multiple cytokines have not been correlated with a history of RBC alloimmunization in at least two studies of people with SCD ( 80 , 104 ); studies of serum cytokine profiles at the time of new antibody formation, though logistically difficult to coordinate, might be more informative.…”
Section: Characteristic Of Cell Subsets As Related To Alloimmunizatiomentioning
confidence: 99%
“…Wnts secreted from monocytes may be important for preserving a functional cytoskeleton and maintaining the correct number of erythrocytes, which may be affected in monocytosis implicated in anemia and sickle cell disease. [104][105][106][107] Interestingly, in patients with sickle cell disease, RBC alloimmunization is associated with lower expression of specific monocyte markers, 108 and it is tempting to speculate that the secretion of Wnt from this monocyte subpopulation may be affected.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies identified a reduced number of PD1 + CXCR5 + circulating T follicular helper (Tfh) cells (including Tfh subsets) among alloimmunized compared with nonalloimmunized individuals ( 49 ). Further examination suggested that responders may also have lower expression of Fc gamma receptor type 1 (FcγR1) on classical and intermediate monocytes than nonresponders( 50 ).…”
Section: In Vitro Human Studies—the Responder–nonresponder Continuummentioning
confidence: 99%